The logic of professionalism : work and management in professional service organizations - Alvehus, Johan (Bristol University Press, 2021)
"This book discusses common management and work practices in professional service organizations. Alvehus opens important discussions on what it means to work, manage, and be managed in such professional organizations, casting light on classic conflicts. He takes everyday work as a starting point and adopts a critical view that focuses on challenges and struggles in both public and private settings. He offers new perspectives and key insights for the future of professionalism."--